ANSWER
![\begin{gathered} f(6)=-40 \\ x=+4;x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ga7knvcz3hf8ajmgez4i03uaq3h3yr5x1g.png)
Step-by-step explanation
We have that:
![\begin{gathered} f(x)=-9x+14 \\ g(x)=-3x^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qpqvpyukb27atyugv551iff2e8cxbuo6wg.png)
To find the value of f(6), we have to substitute 6 into f(x). That is:
![\begin{gathered} f(6)=-9(6)+14 \\ f(6)=-54+14 \\ f(6)=-40 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ihklp11w9kma0eb8s5yqo5kqri3c1epiay.png)
That is the value of f(6).
To find the values of x when g(x) =-48, we have to substitute -48 for g(x) in the function and solve for x:
![\begin{gathered} -48=-3x^2 \\ \Rightarrow x^2=(-48)/(-3) \\ x^2=16 \\ \Rightarrow x=\pm\sqrt[]{16} \\ x=+4;x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wdrfmek3palxx7hmw0mt8stwhmtvellvse.png)
Those are the values of x for g(x) = -48